What is Effective Pedagogy for multilingual learners? Observations of teaching that challenges inequity—the OPETAN project in England - Perumal Ratha; Flynn Naomi; Viesca Kara Mitchell; Ennser-Kananen Johanna; Routarinne Sara (Routledge, 2022)
There is little empirical evidence regarding how best to prepare general education teachers for the challenge of supporting multilingual learners. This is both regarding helping learners develop the language of schooling, and achieving academic success (Faltis & Valdés, 2016). Similarly, little is known about what in-service teachers should know, and what pedagogical perspective they should adopt, to achieve these aims (Faltis & Valdés, 2016; Takanishi & Le Menestrel, 2017). However, there is a promising line of research that proposes an observation tool to evaluate classroom pedagogy: ‘The Standards for Effective Pedagogy’ (the ‘Standards’ 2014; Teemant, 2015). The OPETAN project (Observations of Pedagogical Excellence of Teachers Across Nations), based in Germany, Finland, the United States, and England, draws on these Standards, which derive from sociocultural perspectives, and presents a portrait of how they work in practice. This chapter reports on the project’s findings in England. Teachers in four primary schools were selected on the basis of their recognised competent pedagogical practice with multilingual learners in culturally and linguistically diverse classrooms. The pupils were aged between four and 11. Drawing on qualitative methods, classroom observation data were gathered and thematically analysed in the light of the descriptors of the ‘Standards for Effective Pedagogy’. In this chapter, key themes from the data are presented and three teaching vignettes selected to illustrate the pedagogy observed. The findings identify pedagogies teachers can use to better support multilingual learners.
Multilingual Approaches for Teaching and Learning : From Acknowledging to Capitalising on Multilingualism in European Mainstream Education